[Procedures for the environmental remediation of contaminated sites in Italy: food for thought from the Roundtable at Flowpath 2021 in Naples] - Diego Di Curzio; Marco Rotiroti; Elisabetta Preziosi (Acque Sotterranee, 2022)
[This technical note follows the discussion that took place during the Roundtable on “Experiences and perspectives on groundwater contamination: from characterization to legal implications”, held during the National Conference Flowpath 2021, which was attended by experts in the field of contaminated sites from the academic, professional, and public sectors. This contribution aims at summarizing and discussing the critical points emerged during the Roundtable, starting from the description of the technical-administrative procedure currently required by the Italian legislation and the measures suggested for each phase of the environmental remediation process.]